Baseline measures of primary health care team functioning and overall primary health care performance at Du Noon Community Health Centre - Shapi Mukiapini; Graham Bresick; Abdul-Rauf Sayed; Cynthia Le grange (AOSIS, 2018)
Background: Research consistently demonstrates the importance of effective team work for improving the quality of health care. We conducted a baseline measure of primary health care (PHC) team effectiveness and overall PHC performance at a primary care facility. Aim: To improve PHC team effectiveness and ultimately the quality and user experience of primary care at a community health centre (CHC). Setting: Du Noon CHC in the southern and western substructure of the Cape Town Metro district services (MDHS). Methods: A cross-sectional study using a combination of the Nominal Group Technique (NGT) consensus method and the South African Primary Care Assessment Tool (ZA PCAT) to assess PHC team effectiveness and PHC organisation and performance. Results: The ZA PCAT was administered to 110 CHC users (patients) and 12 providers (doctors and clinical nurse practitioners). Data from 20 PHC team members showed they perceived their team as well functioning (70% agreement on a 7-item PHC team assessment tool incorporated into the ZA PCAT). The NGT method achieved participant (20) consensus on communication and leadership as the main challenges to effective team functioning and on ideas to overcome the challenges. The ZA PCAT user data showed 18.2% of users rated first contact access as acceptable to good; 47.3% of users rated ongoing care as acceptable to good. Provider data showed that 33% of providers rated first contact access as acceptable to good; 25% of providers rated ongoing care as acceptable to good. First contact access received the lowest acceptable to good score (18.2%) and comprehensiveness (services available) the highest score (88.2%) from users. For the providers, the lowest acceptable to good score was for ongoing care (25%) and the highest acceptable to good score was for primary health care team availability (100%). The ZA PCAT total primary scores were good (above 60%) for both users and providers but moderately higher for the providers. Conclusion: Knowledge of how teams perceive their effectiveness can motivate them to generate ideas for improving performance. There were discrepancies between providers' assessment of team functioning using the ZA PCAT measure and the NGT method results. The ZA PCAT also showed differences between providers' and users' perceptions of PHC performance - consistent with the findings of the multi-CHC Western Cape ZA PCAT study. These findings should encourage and support CHC and district level staff in their efforts to improve the quality and user experience of primary care, as well as PHC team performance.